If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25.294 + -0.8x = -3.2 + 2.7(2.7x + 5.6) Reorder the terms: -25.294 + -0.8x = -3.2 + 2.7(5.6 + 2.7x) -25.294 + -0.8x = -3.2 + (5.6 * 2.7 + 2.7x * 2.7) -25.294 + -0.8x = -3.2 + (15.12 + 7.29x) Combine like terms: -3.2 + 15.12 = 11.92 -25.294 + -0.8x = 11.92 + 7.29x Solving -25.294 + -0.8x = 11.92 + 7.29x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7.29x' to each side of the equation. -25.294 + -0.8x + -7.29x = 11.92 + 7.29x + -7.29x Combine like terms: -0.8x + -7.29x = -8.09x -25.294 + -8.09x = 11.92 + 7.29x + -7.29x Combine like terms: 7.29x + -7.29x = 0.00 -25.294 + -8.09x = 11.92 + 0.00 -25.294 + -8.09x = 11.92 Add '25.294' to each side of the equation. -25.294 + 25.294 + -8.09x = 11.92 + 25.294 Combine like terms: -25.294 + 25.294 = 0.000 0.000 + -8.09x = 11.92 + 25.294 -8.09x = 11.92 + 25.294 Combine like terms: 11.92 + 25.294 = 37.214 -8.09x = 37.214 Divide each side by '-8.09'. x = -4.6 Simplifying x = -4.6
| 2[3-(p+6)]-18=4(3+p) | | x^3-4x-5760=0 | | 4m-2=4m-14 | | 0.5(6x+10)+8=10 | | 20x-5x+2x=190 | | 1.88=4.9t^2 | | 8x-(-5x)+3=x-7+10 | | (8x+24)-4x=(4x+96)-4x | | 0.25x+0.15=2.00 | | 7(x+3)-6=-8(x-6) | | 3(0.6+2n)+3.2=7.6 | | 60-11=x | | 3x^2+4x-4.75=0 | | 9=6x-10 | | 4+3(b+4)=-5(2b-11) | | 4.3-1.4(y+7)=-9.7 | | 4w^4+16w^2+15= | | 2(a-8)=-22+2a | | x+22=37.5 | | 5=6x-10 | | 4=6x-10 | | 3x=12.4 | | 22-4d=38 | | -10x^2-11x-3=0 | | 8(1+7x)=8-5x | | 2(b+3)=18 | | 4x^2-9=-16x | | 9(x+4)-2(3x-1)=50 | | -20=5g | | 2(7+7x)=14-x | | 2(3n+6)=3(12-2n) | | 3(4+x)=2x-5 |